Analysis of Character Development, Religious, Nationalistic, and Global Perspective Through Civic Education - Andi Aco Agus; Muhammad Amin; Dalilul Falihin; Khaedir Khaedir; A. Rizal (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to analyze how civic education can develop students' characters in terms of religious, nationalistic, and global perspectives. The research method employed is a descriptive qualitative approach. Research data were collected through interviews and observations, and then analyzed using data triangulation, adapted from Miles and Huberman, which involved data reduction, data presentation, and data/conclusion verification with MAXQDA 24 software. The results of this study found that the development of the characters of religious, nationalistic, and global perspectives in students through civic education learning is built through the simultaneous interaction of five main elements, namely: (1) the role and competence of teachers; (2) diverse learning models and methods; (3) the integration of religious, nationalistic, and global perspective values; (4) holistic assessment and evaluation; and (5) learning environment and school culture. This model offers a conceptual renewal for the revitalisation of civic education in the 21st century, while strengthening the Pancasila Student Profile as citizens who are faithful, love their country, and have a global perspective.